Analisis Dan Evaluasi Perpajakan Pada Pelaksanaan Asian Games Tahun 2018 - Indra Bayu; Trinandari Prasetya Nugrahanti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2020)
This purpose of this study is to describe the taxation treatment related to the Olympic Council of Asia (OCA) as the owner of exclusive rights to the Asian Games and its Affiliates, Ticket Taxes, Sponsorship Taxes, Import Duties and Taxes and the obstacles faced in fulfilling tax obligations in the implementation of the 2018 Asian Games. This research method uses descriptive qualitative to describe the tax treatment of OCA and its affiliates, ticket tax, sponsorship tax, Import Duty and Taxes in the 2018 Asian Games regarding Sugiyono's opinion. This research was taken in January 2018 until 31 December 2018 using primary and secondary data. The available data is then processed using qualitative data analysis methods involving 4 respondents who are considered to be able to represent conclusions. The results of this study are for the host of the imposition of taxes, duties and levies imposed directly or indirectly by law as a result of organizing the 2018 Asian Games burden in terms of financing, but the authority of the OCA as the holder of exclusive rights to the Asian Games is an exception to the provisions general rules in Indonesia. In addition there is a tax exemption for sales of tickets, tax sponsorship and import duties and taxes during the 2018 Asian Games which is a solution to the limited funds by INASGOC. Even though the Indonesian government lost the potential for tax revenue, during the 2018 Asian Games, the direct and indirect economic impact was valued at 83 Trillion Rupiah (BAPPENAS, 2018). This means that the economic impact of the 2018 Asian Games is more beneficial than the tax compensation given to the OCA or INASGOC. Keyword : Tax, Asian Games, Duties, INASGOC.